The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1136/bmjopen-2020-044884
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between obesity and lower rates of breast feeding initiation in regional Victoria, Australia: an 8-year retrospective panel study

Abstract: ObjectivesUsing routinely collected hospital data, this study explored secular trends over time in breast feeding initiation in a large Australian sample. The association between obesity and not breast feeding was investigated utilising a generalised estimating equations logistic regression that adjusted for sociodemographics, antenatal, intrapartum and postpartum conditions, mode of delivery and infant’s-related covariates.DesignPopulation-based retrospective panel.SettingA regional hospital that serves 26% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The study sample and setting have been described previously [ 18 ]. Briefly, all women birthing at a large tertiary hospital in regional Victoria, Australia between January 2010 and December 2017 were eligible for inclusion.…”
Section: Methodsmentioning
confidence: 99%
“…The study sample and setting have been described previously [ 18 ]. Briefly, all women birthing at a large tertiary hospital in regional Victoria, Australia between January 2010 and December 2017 were eligible for inclusion.…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of obesity and overweight are increasing worldwide (NCD Risk Factor Collaboration, 2017) and are linked to lower breastfeeding rates (Ramji et al, 2018;Mangel et al, 2019). In Australia, women with obesity were reported to have 9% less breastfeeding initiation (Bish et al, 2021), and lower breastfeeding initiation rates have also been reported in the United States (Kair & Colaizy, 2016) and France (Boudet-Berquier et al, 2018). A lower likelihood of sustained breastfeeding among women with high BMIs also has been reported as prevalent globally (Boudet-Berquier et al, 2018;Chen et al, 2020;Joham et al, 2016).…”
Section: Introductionmentioning
confidence: 99%